2021
DOI: 10.3390/math9151748
|View full text |Cite
|
Sign up to set email alerts
|

Power Spectral Density Analysis of Nanowire-Anchored Fluctuating Microbead Reveals a Double Lorentzian Distribution

Abstract: In this work, we investigate the properties of a stochastic model, in which two coupled degrees of freedom are subordinated to viscous, elastic, and also additive random forces. Our model, which builds on previous progress in Brownian motion theory, is designed to describe water-immersed microparticles connected to a cantilever nanowire prepared by polymerization using two-photon direct laser writing (TPP-DLW). The model focuses on insights into nanowires exhibiting viscoelastic behavior, which defines the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Relying on the fluctuation-dissipation theorem, the proposed mechanical model was complemented by random forces to explain the stochastic motion of the microbeads attached to viscoelastic nanowires. The double-Lorentzian power spectral density, derived from the model, was well reproduced by experimental observations [28].…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Relying on the fluctuation-dissipation theorem, the proposed mechanical model was complemented by random forces to explain the stochastic motion of the microbeads attached to viscoelastic nanowires. The double-Lorentzian power spectral density, derived from the model, was well reproduced by experimental observations [28].…”
Section: Introductionsupporting
confidence: 59%
“…Subsequently, the trapping laser beam was switched off and the microbead motion was followed by video tracking. To suppress the effect of Brownian fluctuations [28], the results of twelve repetitive recovery actions were averaged for each glucose concentration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the cantilever mechanics can be described by a three-parameter viscoelastic model. Furthermore, an analytical solution for the power spectral density of freely fluctuating viscoelastic cantilever/microsphere structures immersed in Newtonian liquids was obtained 42 . After being refined, this result serves as a theoretical basis for the presented viscometers.…”
Section: Methodsmentioning
confidence: 99%
“…al. [23] explained the process of development of the model in the domain of mechanics in a sophisticated way. Different types of computer simulation are delineated in a versatile way.…”
Section: Dynamics Of Mechanical System-a Literature Reviewmentioning
confidence: 99%